2004
DOI: 10.1007/s00216-003-2471-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of reconstruction induced changes of surface stress for Sb on Si(111)

Abstract: With the combination of high resolution low energy electron diffraction and a bending sample technique we have simultaneously studied surface stress and surface structure during adsorption and desorption of antimony on the Si(111) surface. During desorption, several surface reconstructions with significantly different effects on the stress signal evolve. The surface stress of all observed structures has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The detailed study on the similar surface condition is reported elsewhere. [16][17][18][19][20][21][22] Figure 6 displays the UHV-STM image on the submonolayer of CuPc deposited on the prepared substrate above. The Sb passivated surface (dark) and CuPc domains (white) can be seen at the same time which confirms the submonolayer deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed study on the similar surface condition is reported elsewhere. [16][17][18][19][20][21][22] Figure 6 displays the UHV-STM image on the submonolayer of CuPc deposited on the prepared substrate above. The Sb passivated surface (dark) and CuPc domains (white) can be seen at the same time which confirms the submonolayer deposition.…”
Section: Resultsmentioning
confidence: 99%